Earnings management and board characteristics: evidence from Malaysia - Norman Mohd. Saleh; Takiah Mohd. Iskandar; Mohd. Mohid Rahmat (Penerbit Universiti Kebangsaan Malaysia, 2005)
The Malaysian Code of Corporate Governance was introduced to improve the monitoring function of the board of directors, audit committee and the external audit. This study assesses the effectiveness of some board characteristics to monitor management behavior with respect to their incentives to manage earnings. We found discretionary accruals as a proxy for earnings management is negatively related to management ownership, but positively related to the existence of CEO-Chairman duality, after controlling for size, leverage and performance. The result shows multiple directorships factor is negatively related to earnings management proxy only in firms with negative unmanaged earnings. This implies multiple directorships factor is effective to detect earnings management practices to avoid losses. Examination of the data also shows that the ratio of independent board members is not significantly related to earnings management in firms with duality status